Genomic footprints of selection in early-and late-flowering pearl millet landraces - Faye, Adama; Barnaud, Adeline; Kane, Ndjido Ardo; Cubry, Philippe; Mariac, Cédric; Burgarella, Concetta; Rhoné, Bénédicte; Faye, Aliou; Olodo, Katina Floride; Cisse, Aby; Couderc, Marie; Dequincey, Anaïs; et al. (Frontiers in Plant Science, 2022)
Pearl millet is among the top three-cereal production in one of the most climate vulnerable regions, sub-Saharan Africa. Its Sahelian origin makes it adapted to grow in poor sandy soils under low soil water regimes. Pearl millet is thus considered today as one of the most interesting crops to face the global warming. Flowering time, a trait highly correlated with latitude, is one of the key traits that could be modulated to face future global changes. West African pearl millet landraces, can be grouped into early- (EF) and late-flowering (LF) varieties, each flowering group playing a specific role in the functioning and resilience of Sahelian smallholders. The aim of this study was thus to detect genes linked to flowering but also linked to relevant traits within each flowering group. We thus investigated genomic and phenotypic diversity in 109 pearl millet landrace accessions, i.e. 66 early-flowering and 43 late-flowering, grown in the groundnut basin, the first area of rainfed agriculture in Senegal dominated by dry cereals (millet, maize, sorghum) and legumes (groundnuts, cowpeas). We were able to confirm the role of PhyC gene in pearl millet flowering and identify several other genes that appear to be as much as important, such as FSR12 and HAC1. HAC1 and two other genes appear to be part of QTLs previously identified and deserve further investigation. We were able to highlight a several alleles that could contribute to the improvement of pearl millet yield, especially since their impact was demonstrated across flowering cycles.